Ecological risk assessment of heavy metal contamination in Xiaohai Lagoon, Hainan island, China - Eunice Mutethya; Qi Liu; Edwine Yongo; Zhiqiang Guo; Hui Yu; Yunyu Zhang; Zhiyuan Lu; Changqing Ye (Frontiers in Marine Science, 2025)
Xiaohai Lagoon has faced significant natural and anthropogenic pressures, necessitating a heavy metal contamination assessment. Sediment and water samples were collected in 2024 during dry and wet seasons to assess heavy metal pollution and ecological risk based on individual and synergistic indices. Heavy metal content was detected using an inductively coupled plasma mass spectrometer. The Cr, Zn, Pb, Cd, Cu, Ni, As, and Hg in water ranged from 0.90 to 9.08, 4.52 to 49.48, 0.01 to 7.26, 0.00 to 1.33, 0.87 to 61.90, 0.03 to 13.23, 1.16 to 3.04, and 0.01 to 2.00 µg L -1 , respectively. The average heavy metal concentration in water was within acceptable limits. For sediments, Cr, Zn, Pb, Cd, Cu, Ni, As, and Hg contents ranged from 1.98 to 40.60, 8.50 to 90.31, 3.12 to 61.62, 0.00 to 0.25, 0.50 to 76.38, 1.31 to 17.23, 1.27 to 9.41, and 0.00 to 0.06 mg kg -1 , respectively. Sediment metals, except Cd, met China’s primary standards and varied seasonally, with peaks in the dry season. The average geoaccumulation index ( I geo ) values for all the metals, except As, were below 0, while the pollution load index ( PLI ) suggested moderate pollution. Additionally, the contamination factor ( CF ) reflected moderate pollution for Cd and Hg, while As reflected a considerable pollution level. Further, Pearson’s and PCA analyses revealed that Cr, Zn, Pb, Cd, Ni, As, and Hg correlated positively, possibly from aquaculture and agricultural inputs, while Cu derived from urban sources. The study provides critical data for informed management of the Xiaohai Lagoon.

Comprehensive distribution of Se in yellowfin tuna dark meat and characterization of its Se-enriched water-soluble protein - Hui Yu; Meiting Xian; Caiye Qu; Pai Peng; Edwine Yongo; Guanghua Xia; Juan Xiao; Zhiqiang Guo (Food Chemistry, 2025)

Comparative energy metabolism in red and white muscles of juvenile yellowfin tuna, Thunnus albacore - Zhiyuan Lu; Qian Li; Edwine Yongo; Juan Xiao; Zhiqiang Guo (Frontiers in Marine Science, 2025)
The musculature of yellowfin tuna ( Thunnus albacares ) exhibits distinct functional specialization, with slow-twitch oxidative red muscle and fast-twitch glycolytic white muscle demonstrating marked disparities in energy metabolic characteristics. To elucidate the molecular mechanisms underlying these functional divergences, this study implemented an integrated approach incorporating ultrastructural analysis via transmission electron microscopy (TEM), transcriptomic profiling, and enzymatic activity assays of key metabolic regulators. TEM imaging revealed that red muscle fibers contain larger mitochondria and prominent lipid droplets compared to white muscle fibers. Our transcriptome analysis identified 3,162 genes with significant expression differences-1,515 were up-regulated, and 1,647 were down-regulated. Functional enrichment analysis demonstrated significant association of red muscle DEGs with oxidative phosphorylation, tricarboxylic acid cycle, and fatty acid β-oxidation, while white muscle preferentially enriched glycolysis/gluconeogenesis pathways. Enzymatic validation revealed red muscle exhibited higher citrate synthase activity (2.3-fold) and elevated β-hydroxyacyl-CoA dehydrogenase levels (1.8-fold), whereas white muscle showed greater hexokinase activity (4.7-fold) and increased lactate dehydrogenase activity (3.2-fold). These findings provide novel insights into the physiological adaptations underlying the distinctive swimming strategies of scombroid fishes, revealing evolutionary optimization of muscle metabolic pathways corresponding to their sustained cruising capacity and burst swimming performance.

Ecological health assessment using zooplankton index of biotic integrity (Z-IBI) in urban rivers in Hainan Island, China - Eunice Mutethya; Edwine Yongo; Pengfei Zhang; Zhiqiang Guo; Ye Changqing (Environmental Monitoring and Assessment, 2024)

Assessing ecological status using phytoplankton functional groups in three urban rivers in Hainan Island, China - Edwine Yongo; Eunice Mutethya; Ji Xu; Hui Yu; Yu Wenhui; Zhiqiang Guo (Environmental Science and Pollution Research, 2024)

Spatial and seasonal dynamics of zooplankton functional groups and their relationship with environmental factors in urban rivers in Haikou City, China - Eunice Mutethya; Edwine Yongo; Liu Qi; Liu Xiaojin; Zhiqiang Guo; Ye Changqing (Limnologica, 2024)

Novel Se-enriched α-glucosidase inhibitory peptide derived from tuna dark meat: Preparation, identification and effects on IR-HepG2 cells - Hui Yu; Meiting Xian; Caiye Qu; Pai Peng; Edwine Yongo; Zhiqiang Guo; Zhixun Du; Juan Xiao (Food Bioscience, 2024)

Spatio-temporal dynamics of phytoplankton community structure in the coastal waters of the Southern Beibu Gulf - Haipeng Pang; Edwine Yongo; Zhiyuan Lu; Qian Li; Xiaojin Liu; Liang Li; Zhiqiang Guo (Environmental Monitoring and Assessment, 2024)

WITHDRAWN: Heavy metal bioaccumulation, stable isotope ratios, and human health risks of fishes from urban rivers in Haikou City, China - Eunice Mutethya; Edwine Yongo; Yu Wenhui; Ji Xu; Hui Yu; Zhiqiang Guo (Limnologica, 2023)

Effects of substrate on burrowing behavior, feeding physiology, and energy budget of undulated surf clam Paphia undulata - Pengfei Zhang; Edwine Yongo; Fei Liu; Shuai Pan; Anfu Sun; Long Zhou; Zhiqiang Guo; Caihuan Ke (Journal of Oceanology and Limnology, 2023)

Spatio-temporal variation in water quality and phytoplankton community structure in Changwang, Meishe, and Wuyuan Rivers in Hainan Island, China - Edwine Yongo; Eunice Mutethya; Fangfang Jin; Pengfei Zhang; Sovan Lek; Ling Mo; Jingquan Li; Zhiqiang Guo (Environmental Monitoring and Assessment, 2023)